Detection of BCR/ABL Fusion Gene Based on MNAzyme‐mediated Target‐cycling and ssDNA‐assisted Cascade Hybridization Reaction. Issue 10 (2nd August 2018) - Duan, Yu; Yuan, Taixian; Xu, Yongjie; Zhao, Min; Guo, Bin; Cheng, Wei; Ding, Shijia
Abstract: A novel and simple electrochemical strategy has been developed for ultrasensitive and specific detection of BCR/ABL fusion gene based on multi component nucleic acid enzyme (MNAzyme) and ssDNA‐assisted cascade hybridization reaction. In the presence of Mg 2+, a stable active MNAzyme was formed by the homogeneous recognition and specific binding with the target, initiating shear reaction of hairpin probe (HP) to produce numerous triggers. These triggers could hybridize with the immobilized capture probes and the biotinylated P1 and P2, which caused the heterogeneous ssDNA‐assisted cascade hybridization reaction on the surface of the electrode. Binding with the biotin‐rich long concatamers structure, streptavidin‐alkaline phosphatase (ST‐AP) could catalyze α‐naphthyl phosphate (α‐NPP) to produce amplified electrochemical signals. The electrochemical DNA biosensor showed high sensitivity for target gene with detection limit of 2.19×10 −14 M. In addition, the established biosensor was successfully applied for detecting target BCR/ABL gene in complex samples. Thus, the electrochemical biosensing strategy presents a simple and pragmatic platform toward ultrasensitive fusion gene detection in chronic myelogenous leukemia (CML) diagnosis. Abstract :